Randomization in N-of-1 clinical trials: Is it possible to draw causal inferences from single-patient data? - Onghena, Patrick (Henry Stewart Talks, 2016)
Definitions and examples of N-of-1 clinical trials, Randomization and blinding of N-of-1 clinical trials, Classification of N-of-1 design, Designing N-of-1 clinical trials to draw casual inference, Current consensus & the importance of randomization, Generalizability: problems with N-of-1 clinical trials and RCTs